2011
DOI: 10.1002/zoo.20330
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between gonadal steroid hormones and vulvar bleeding in southern tamandua, Tamandua tetradactyla

Abstract: This study aimed at demonstrating the profiles of circulating gonadal steroid hormones during the estrous cycle and pregnancy in a southern tamandua (Tamandua tetradactyla). Additionally, this study clarified the relationship between vulvar bleeding and hormonal changes. The concentrations of serum progesterone (P(4)) and estradiol-17β (E(2)) were determined by enzyme immunoassays. Serum P(4) and E(2) concentrations changed cyclically and the estrous cycle length (± SD) based on the E(2) cycles was 44.3 ± 4.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 4 publications
1
6
1
Order By: Relevance
“…Females in our study had similar gestational lengths as previously reported for giant anteaters and longer than reported for tamandua [1,3,10,27] (Table 3). By examining three complete pregnancies, we were able to confirm that elevated concentrations of fecal estrogens and P4 occured only during the late gestational period as previously summarized by Patzl et al [10].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Females in our study had similar gestational lengths as previously reported for giant anteaters and longer than reported for tamandua [1,3,10,27] (Table 3). By examining three complete pregnancies, we were able to confirm that elevated concentrations of fecal estrogens and P4 occured only during the late gestational period as previously summarized by Patzl et al [10].…”
Section: Discussionsupporting
confidence: 89%
“…These changes also initiate a secondary surge in progestagens during late pregnancy by luteal cells, the feto–placental unit, or another extra–gonadal source following implantation [30,34]. Elevation of fecal estrogens during late pregnancy in xenarthrans and other species also supports fetal development, and is the result of greater aromatase activity in the corpus lutea and the placenta, as well as the result of increased hepatic clearance of estrogens prior to fecal excretion [10,13,27,34,35]. Fecal estrogens and progestagens returned to baseline levels within 11 days of parturition, and estrous cycling post–partum was observed to resume in as little as 60 days similar to that reported by Patzl et al [10].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, such a method warrants a solid validation if applied in a species for the first time (Palme et al, ; Touma & Palme, ; Sheriff et al, ). To our best knowledge, this hormone monitoring strategy has not been employed in the collared anteater to study adrenocortical response to stressors; only a few studies have been conducted to test other steroids in collared anteaters (Hay et al, ; Kusuda et al, ) or other species of the superorder (Mühlbauer et al, ; Superina et al, ; Howell‐Stephens et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of the changes in the vulval appearance during the oestrous cycle was conducted according to the methodology previously reported for the Southern Tamandua ( Tamandua tetradactyla ; Kusuda et al., ). Examination of the vulval appearance included the observation and subsequent description of the labia and commissures of the vulva, and mucus in the vestibulum vaginae.…”
Section: Methodsmentioning
confidence: 99%